Accounts concerning Allocation of Provisions for Offerings in the Ningal-Temple at Ur - Figulla, H. H.
Tablets with a simple formula — the simple formula expanded — with a more elaborate formula — offerings to minor gods — offerings at festivals — with an unusual formula.